Historias de vida sobre el proceso de conversión religiosa en Alcohólicos Anónimos - Gutiérrez Portillo, Ángel Alejandro (Facultad de Trabajo Social y Desarrollo Humano, 2022)
The consumption of alcohol is an atavistic practice that is deeply rooted in contemporary society in Mexico. Based on the reports of the Ministry of Health, in the last two decades, the consumption of intoxicating beverages is a problem that has worsened in the country, because the number of subjects dependent on ethyl alcohol has increased considerably. For your care, there are different therapeutic methods. However, one of the most popular is outpatient treatment in its self-help and mutual aid group modality. Under this scheme Alcoholics Anonymous is the one with the greatest presence at the national level. An important part of the Alcoholics Anonymous recovery program is when adherents tell their life stories, since this practice causes a catharsis that is part of the process of religious conversion in members of Double A